The Influence of Organizational Culture and Job Satisfaction on Employee Performance at PT. Mega Sentosa Prima in Jakarta - Nariah Nariah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
Organizational culture has a close relationship with the effectiveness of the organization in achieving its goals. A good organizational culture always impacts on organizational effectiveness. This study aims to determine the effect of organizational culture and job satisfaction on employee performance at PT. Mega Sentosa Prima in Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study organizational culture significantly influence employee performance by 42.1%, hypothesis testing obtained t count> t table or (8.335>> 1.989). Job satisfaction has a significant effect on employee performance by 44.4%, the hypothesis test obtained t count> t table or (8,764> 1,989). Organizational culture and job satisfaction simultaneously have a significant effect on employee performance by 53.2%, the hypothesis test is obtained F count> F table or (53.979> 2.770).